Exploring how the use of a mini-ecosystem enables and/or constrains grade 5 learners to make sense of scientific inquiry - Tobias, Ruusa Taimi (Rhodes University, Faculty of Education, Department of Education)
The Namibian Science curriculum clearly states that learning of science should be promoted through using inquiry-based approaches. However, it does not state how teachers should go about promoting inquiry-based approaches in their classrooms, especially in under-resourced rural schools. This is exacerbated in part by the fact that there is inadequate or lack of professional development for science teachers which focus in particular on promotion of inquiry-based approaches. As a result, science teachers tend to ignore inquiry-based approaches in their classrooms. It is against this background that my study sought to explore how the use of a 'mini-ecosystem' enables and/or constrains grade 5 learners from an under-resourced rural school to make sense of scientific inquiry. The study is underpinned by an interpretive paradigm. Within the interpretive paradigm, a qualitative case study approach, using the Predict-Explain-Explore-Observe-Explain (PEEOE) framework was adopted. This case study was carried out in an under-resourced rural Namibian school and the participants were grade 5 Natural Science and Health Education learners. I also invited a teacher from the school to be my critical friend and a participant observer. Data were generated using the Views About Scientific Inquiry (VASI) questionnaire, observations, focus group interviews and learners' reflections. Vygotsky's socio-cultural theory was my theoretical framework, and within this theory, I used mediation of learning, social interactions, the zone of proximal development and self-regulation as lenses to analyse my data. A thematic approach to data analysis was adopted. That is, qualitative data were analysed inductively to come up with sub-themes and thereafter common sub-themes were combined to form themes. The findings of the study revealed that the observation of mini-ecosystems enabled learners to interact and participate with each other in their respective groups. Moreover, learners were able to identify some scientific concepts such as evaporation, condensation, water cycle and rainfall. These findings are in contrast with the fact that they seemed to struggle to answer the VASI questionnaire that was conducted prior to observation. The study thus recommends that science teachers should make efforts to use easily accessible resources such as a 'mini-ecosystem' to promote scientific inquiry amongst their learners.
Keywords: Science-- Study and teaching (Elementary)-- Namibia; Health education (Elementary)-- Namibia; Education for sustainable development; Sensemaking; Inquiry-based learning-- Namibia; Terrariums; Social learning-- Namibia